Whose Responsibility is it to PrEP for Safe Sex? Archaic HIV Criminalization and Modern Medicine - Brigid Bone (Washington University Journal of Law & Policy, 2017)
This Note traces the history of HIV and its impact on the homosexual community, with a focus on criminal statutes that attempted to regulate the actions of individuals with HIV, and how those statutes can be evaluated considering modern advancements against the virus. Bone addresses the state of HIV criminalization bearing in mind medical treatments, such as Highly Effected Antiretroviral Treatment (HAART) and Pre-Exposure Prophylaxis (PrEP), as well as conviction rates among those who engage in sexual activity while HIV positive. Bone proposes amending current criminalization statutes in a way that would de-stigmatize the conversation that surrounds the virus while creating a statutory system that would better combat HIV transmission.
Keywords: anti-retroviral medications; sexual activity; AIDS; criminalization; HIV; homosexuality; criminal statutes; regulations; Highly Effected Antiretroviral Treatment; HAART; Pre-Exposure Prophylaxis; PrEP